White Organic Light Emitting Diodes with a Random Scattering Layer for an Internal Light Extraction. (10th October 2015) - Shin, Jin-Wook; Moon, Jaehyun; Cho, Doo-Hee; Joo, Chul Woong; Park, Seung Koo; Lee, Jonghee; Han, Jun-Han; Cho, Nam Sung; Cho, Hyunsu; Lee, Jeong-Ik
Abstract : A random scattering layer (RSL) containing random nano-structures as the internal light extraction functional layer was introduced into white organic light-emitting diodes (OLEDs) to improve the light extraction efficiency and preserve the white color quality. White OLEDs on the RSL with varying heights of nano-structures were successfully fabricated, and the effects of haze on the characteristics of the OLED device were investigated. The haze and light extraction efficiency were mutually proportional. The RSL equipped white OLEDs exhibited an external quantum efficiency improvement of 41.5% with a low angular spectrum change. The results from our RSL are interpreted as an optical functionality which reduces the internal wave guiding mode due to the scattering effect leading to enhanced device efficiency and stabilized emission spectra, respectively.